2009
DOI: 10.1577/t08-149.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroshock on Cyprinid Embryos: Implications for Threatened and Endangered Fishes

Abstract: The purpose of this study was to evaluate the effects of electroshock on survival to hatching in embryos of Cyprinidae, which includes numerous fish species designated as threatened or endangered under the U.S. Endangered Species Act. Embryos of three cyprinids were exposed for 20 s to a homogeneous electric field (DC or 60‐Hz pulsed DC [PDC], 3‐ms pulse width) at voltage gradients similar to those used during electrofishing. Exposure occurred only once and was at a specific stage of development. Zebrafish Dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Based upon simulation modelling, MacKenzie & Royle (2005) developed a table yielding the optimum number of surveys per site (K) for different combinations of occupancy and detection; optimum refers to a design that minimises variance in the occupancy estimate by balancing the trade-off between sampling intensively at a few sites or less intensively at many sites. This is important given the cost of sampling and the risk of mortality associated with electrofishing (e.g., Bohl et al 2009). Similarly, using our estimated values of p, w, K and equation 6.3 in MacKenzie et al (2006), the number of sites needed to achieve a desired level of precision can be estimated.…”
Section: Applications To Future Monitoringmentioning
confidence: 99%
“…Based upon simulation modelling, MacKenzie & Royle (2005) developed a table yielding the optimum number of surveys per site (K) for different combinations of occupancy and detection; optimum refers to a design that minimises variance in the occupancy estimate by balancing the trade-off between sampling intensively at a few sites or less intensively at many sites. This is important given the cost of sampling and the risk of mortality associated with electrofishing (e.g., Bohl et al 2009). Similarly, using our estimated values of p, w, K and equation 6.3 in MacKenzie et al (2006), the number of sites needed to achieve a desired level of precision can be estimated.…”
Section: Applications To Future Monitoringmentioning
confidence: 99%
“…Snorkel sampling has an obvious advantage over electrofi shing because it greatly reduces handling stress and mortality, which is an important consideration when assessing the status of imperiled fi shes (Bohl et al 2009, Jordan et al 2008, Poos et al 2007). Our study indicated that the relative effectiveness of these two methods differed among species and that snorkel sampling was comparable or in some cases superior to electrofi shing for estimating site occupancy.…”
Section: Snorkel Sampling Versus Electrofi Shingmentioning
confidence: 99%
“…This problem was ignored in the past, but it is becoming increasingly more common to account for incomplete species detection in surveys for rare fi shes (e.g., Albanese et al 2007, Burdick et al 2008, Wenger et al 2008. Another challenge is the need to minimize handling stress and the risk of mortality for legally protected fi shes (Jordan et al 2008), which may restrict or preclude the use of effective but potentially harmful sampling methods such as electrofi shing (Bohl et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Previous research into the effects of electricity on fish embryo survival has been conducted by exposing embryos to electrical fields once and then monitoring survival (e.g., Cho et al 2002;Henry and Grizzle 2004;Bohl et al 2009;Bohl et al 2010 electrofishing (e.g., Bohl et al 2009) and pores do not close immediately after the electrical field is removed, it is possible that multiple exposures to electrical fields could increase embryo mortality by sustaining pores over a longer period of time that can "leak" cytoplasmic contents into the environment (e.g., Cerda et al 2006). Conversely, increased mortality resulting from multiple exposures of embryos to low-voltage gradients could make efforts to control invasive fish species at early life history stages using electricity more feasible.…”
mentioning
confidence: 99%